Specific fatty acid intake and the risk of pancreatic cancer in Canada - Nkondjock, A (Nature Publishing Group, 2005)
The possible association of specific fatty acid (FA) intake and pancreatic cancer risk was investigated in a population-based case–control study of 462 histologically confirmed cases and 4721 frequency-matched controls in eight Canadian provinces between 1994 and 1997. Dietary intake was assessed by means of a self-administered food frequency questionnaire. Unconditional logistic regression was used to assess associations between dietary FAs and pancreatic cancer risk. After adjustment for age, province, body mass index, smoking, educational attainment, fat and total energy intake, statistically significant inverse associations were observed between pancreatic cancer risk and palmitate (odds ratios (ORs)=0.73; 95% confidence intervals (CIs) 0.56–0.96; P-trend=0.02), stearate (OR=0.70; 95% CI 0.51–0.94; P-trend=0.04), oleate (OR=0.75; 95% CI 0.55–1.02; P-trend=0.04), saturated FAs (OR=0.67; 95% CI 0.50–0.91; P-trend=0.01), and monounsaturated FAs (OR=0.72; 95% CI 0.53–0.98; P-trend=0.02), when comparing the highest quartile of intake to the lowest. Significant interactions were detected between body mass index and both saturated and monounsaturated FAs, with a markedly reduced risk associated with intake of stearate (OR=0.36; 95% CI 0.18–0.70; P-trend=0.001), oleate (OR=0.36; 95% CI 0.19–0.72; P-trend=0.002), saturated FAs (OR=0.35; 95% CI 0.18–0.67; P-trend=0.002), and monounsaturated FAs (OR=0.32; 95% CI 0.16–0.63; P-trend<0.0001) among subjects who are obese. The results suggest that substituting polyunsaturated FAs with saturated or monounsaturated FAs may reduce pancreatic cancer risk, independently of total energy intake, particularly among obese subjects.